2014
DOI: 10.1007/s10853-014-8380-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Sr and Mn incorporated ions on the properties of microwave single- and two-step sintered biphasic HAP/TCP bioceramics

Abstract: The aims of this study were to investigate the effects of Sr-and Mn-doped ions on the sintering behaviors, microstructure and mechanical properties of the bioceramics processed by single-and two-step microwave sintering (MWSSS and MWTSS). Nano-sized calcium hydroxyapatite powders doped with Sr and Mn ions, obtained by modified precipitation synthesis, were isostatically pressed at 400 MPa and processed by MWSSS and MWTSS at different temperatures. In all cases during the sintering, the doped HAP powders turned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Pure HA ceramics sintered at 1100-1250 °C are ~98% dense and feature submicrometric grains of 1 to 10 µm, leading to a compressive strength of 40 MPa and a toughness of 1-1.4 MPa.m 0.5 . Substituting HA with ions such as Zn, Ni, Sr and Mn was found to aid the sintering but leads to thermal decomposition and BCP phases without improvement in toughness [26][27][28]. An increase in toughness to 2.7 MPa.m 0.5 could be nevertheless achieved by sintering HA powders in inert atmosphere [29] or by adding fluoroapatite to retain small nanometric grains after sintering [30].…”
Section: 1| Nanoscale: Control Of the Cap Crystalline Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Pure HA ceramics sintered at 1100-1250 °C are ~98% dense and feature submicrometric grains of 1 to 10 µm, leading to a compressive strength of 40 MPa and a toughness of 1-1.4 MPa.m 0.5 . Substituting HA with ions such as Zn, Ni, Sr and Mn was found to aid the sintering but leads to thermal decomposition and BCP phases without improvement in toughness [26][27][28]. An increase in toughness to 2.7 MPa.m 0.5 could be nevertheless achieved by sintering HA powders in inert atmosphere [29] or by adding fluoroapatite to retain small nanometric grains after sintering [30].…”
Section: 1| Nanoscale: Control Of the Cap Crystalline Phasementioning
confidence: 99%
“…(C,D) Toughness and brittleness index as functions of the grain size in sintered CPCs. Data points extracted from [20,22,26,28,29,[38][39][40].…”
Section: 1| Nanoscale: Control Of the Cap Crystalline Phasementioning
confidence: 99%
“…In an earlier study, an even more drastic, fourfold increase in the fracture toughness, from 0.28 to 1.07 MPa m 1/2 , was detected upon doping the biphasic mixture of HA and β-TCP with Mn sintered down to 0.2% porosity, along with the doubling of hardness, from 2.39 to 4.78 GPa. 38 Another study demonstrated variable contents of HA and β-TCP in their sintered biphasic mixtures as a function of the Mn content in the material and an optimal value (4.3 at. %) at which the amount of β-TCP in it was maximized.…”
Section: Introductionmentioning
confidence: 98%
“…SrHAP (composed of 2 wt% Sr in the preparation) was synthesized using the modified chemical precipitation method, as described in detail previously 27) . SrHAP was used in the XAFS analysis as the reference material.…”
Section: Strontium-containing Hydroxyapatite (Srhap)mentioning
confidence: 99%